"Subclinical atherosclerosis in acromegaly: Possible association with cardiovascular risk factors rather than disease activity". (February 2022) - de Almeida, Maria Cristina Costa; Freire, Claudia Maria Vilas; Nunes, Maria do Carmo P.; Soares, Beatriz Santana; Barbosa, Marcia M.; Giannetti, Alexandre Varella; Zille, Giancarlo Pereira; Miranda, Paulo Augusto Carvalho; Ribeiro-Oliveira, Antonio; Drummond, Juliana Beaudette
Abstract: Objective: Cardiovascular (CV) disease is still a major cause of excessive morbidity and mortality in patients with active acromegaly, which may be attributed to a high prevalence of associated pro-atherosclerotic risk factors. However, a direct effect of GH/IGF-1 excess on the vasculature has been previously suggested, warranting further investigation. The present study was designed to investigate whether chronic GH/IGF-1 excess is associated with an increased prevalence of subclinical atherosclerosis in patients with acromegaly. Design: We measured carotid intima-media thickness (cIMT) and assessed carotid plaques by ultrasonography along with classical CV risk factors in 54 acromegaly patients (34 females, 50 ± 12 years and compared those with 62 (42 females, 53 ± 13 years) age-, sex- and CV risk factors- matched controls. In order to compare cIMT measurements between patients and controls we analyzed common carotid artery far wall data as well as a combined measurement result, which consisted of the mean value of the six different measurements, three at each side. Results: mean ± SD serum GH and IGF-1 levels were 2.76 ± 4.65 ng/mL and 1.7 ± 1.25 x ULN, respectively, in all acromegaly patients. Age, body mass index, blood pressure, lipid levels, fasting glucose and Framingham's global cardiovascular risk score classification were similar comparing patients and controls. Combined median [IQR] cIMT measurements were similar in acromegaly patients and matched controls (0.59 [0.52–0.66] mm vs. 0.59 [0.52–0.69] mm; P = 0.872) as well as in acromegaly patients with active and controlled disease (0.59 [0.51–0.68] mm vs. 0.60 [0.54–0.68] mm; P = 0.385). No significant correlations were observed between cIMT measurements and GH (Spearman r = 0.1, P = 0.49) or IGF-1 (Spearman r = 0.13, P = 0.37) levels in patients with acromegaly. Carotid atherosclerotic plaques prevalence was similar in patients and controls (26% vs. 32%; P = 0.54) as well as in patients with active and controlled acromegaly (22% vs. 30%; P = 0.537). Conclusions: Our data suggest that GH/IGF-1 excess itself is not one of the main drivers of subclinical morphological atherosclerosis changes in patients with acromegaly and that optimal control of acromegaly-associated CV risk factors may preserve vasculature structure even when strict biochemical control is not achieved. Highlights: CIMT measurements were similar in acromegaly patients and CV-matched controls Patients with active and controlled acromegaly displayed similar CIMT measurements Carotid plaques prevalence was similar in acromegaly patients and CV-matched controls Carotid plaques prevalence in acromegaly patients was not associated with disease control